Studi Pembentukan Superkonduktor Ba1-xKxBiO3 Melalui Proses Elektrokimia - Rahmat Hidayat; Darminto Darminto; M.O. Tjia (Indonesian Journal of Physics, 2002)
Superconducting films of Ba1-xKxBiO3 have been synthesized by means of potentiostatic electrochemical method incorporating a post annealing process. The critical temperature was determined from resistivity characterization, while structural characterization was carried out by X-ray diffraction and Scanning Electron Microscopy (SEM) measurements. The resistive transition curves show that Tc0 varies between 10K and 11K and Tcon varies between 13K and 18K depending on the electrode voltage used in the synthesis process. The highest Tc0 of 11K was attained in the sample prepared with electrode voltage of 0,65 V. Further analysis of the data reveals that higher quality sample may result from the synthesis by employing higher electrode voltage and more appropriate annealing process.